Effect of microparticulate silver addition in dental adhesives on secondary caries in vitro - Kraemer, Norbert; Moehwald, Mandy; Luecker, Susanne; Domann, Eugen; Zorzin, José Ignacio; Rosentritt, Martin; Frankenberger, Roland (Clinical Oral Investigations, 2015)
The aim of the present study was evaluate the effect of microparticulate silver additions in adhesives on secondary caries formation using an artificial mouth model.One hundred eight intact human third molars received standardized Class-V resin composite restorations (Filtek Supreme XTE bonded with Syntac, Scotchbond 1 XT, Futurabond M). Adhesives were charged with different amounts of microparticulate silver (0 %/0.1 %/0.5 %). After storage for 4 weeks at 37 °C, teeth were subjected to 10,000 thermocycles (+5 °C and +55 °C), and impressions were taken. Streptococcus mutans 10449 was used in a nutrition medium for secondary caries simulation in a fully automated artificial mouth. After completion of thermocycling and biological load cycling, impressions were taken and replicas were investigated under a light microscope for gap widths at enamel and dentin margins. Evaluation of fluorescence was carried out using a special FITC filter. The demineralization depths at the cavity margin were evaluated using Xpert for Windows working at a pixel distance of 5 ?m.After thermocycling, no difference in gap widths and demineralization depths was found (p > 0.05). After incubation, gap widths and demineralization depths were significantly reduced with higher amounts of silver loading in most of the adhesives (p < 0.05). The 0.5 % silver addition resulted in a slight decrease of secondary caries at resin-dentin margins (p < 0.05).Addition of microparticulate silver in commercially available dental adhesives has the potential of reducing secondary caries.The chosen setup was able to produce secondary caries with a distinct in vivo appearance. Microparticulate silver additions in dental adhesives may have an impact on inhibition of secondary caries.
EVALuna2:24674